Bone mass and muscle strength in female college athletes (runners and swimmers) - Emslander, H. C.; Sinaki, M.; Muhs, J. M.; Chao, E. Y.; Wahner, H. W.; Bryant S. C.; Riggs, B. L.; Eastell, R. (Mayo Clinic Proceedings, 1998)
Whether female college athletes had increased muscle strength and bone mass in comparison with age-matched nonathletic female Ss was determined. A secondary comparison between weight-bearing versus non-weight-bearing exercise participation was made. A comparative statistical analysis of the bone mineral density (BMD) of the total body, lumbar spine, and femoral neck, maximal oxygen uptake (VO2max), muscle strength, and level of physical activity in runners (N = 21), swimmers (N = 22), and control Ss (N = 20). Ss were female college students, 18 to 24 years old, who had had more than 8 normal menstrual cycles during the past year. Implications: Total body BMD and femoral neck BMD are higher in weight-bearing exercises than in non-weight-bearing activities. Swimming exercise has no effect on BMD because it is not a weight-bearing activity. Although swimming is not a bone-building exercise, it can significantly improve shoulder, back, and grip muscle strength.